Death and entrepreneuring in family businesses: a complexity and stewardship perspective. Issue 7 (8th August 2022) - Discua Cruz, Allan; Hamilton, Eleanor
ABSTRACT: Based on the works of Alistair Anderson, this article explores entrepreneuring in the context of entrepreneurial families prior to, and following, the death of a leading family member in business. Until now, literature has suggested that the loss of a leading family member may bring complexity and chaos to ongoing entrepreneurial efforts. Drawing on a complex adaptive system and stewardship perspective, this study examines the role of death in entrepreneuring in four entrepreneurial families. With the loss of a leading family member in business, social processes of adaptation in entrepreneurial trajectories are revealed. Our analysis shows that these processes allow members to reorganize, recalibrate, and reconnect aspects of family and business. Our study contributes to understanding social processes in entrepreneuring by capturing how death can influence entrepreneurial choices and progression over time, focusing on what family entrepreneurs do. Conceptualizing the family as a complex adaptive system contributes to a theoretical perspective of stewardship as fluid and collective.